Os contos de Antia: narrativas intercaladas em Efesíacas, de Xenofonte de Éfeso - Silva Duarte, Adriane da (2019)
Although Xenophon of Ephesus is considered as an author with relatively few literary merits, he stands out for his skill in composing embedded narratives, stories within the main story playing an important role in the action's development. The purpose of this paper is to examine how the author takes advantage of this secondary narratives particularly regarding a singular character, namely, Anthia, the Ephesiaka's heroine, Anthia, who is at once narrator and subject of narratives contained within the novel's major framing narrative. I sustain that such strategy is carried out in a close intertextual connection to the Odyssey and contributes to her characterization as a woman specially endowed for rhetoric and cunning.